NANO YAPILI TİTANYUM DİOKSİT İNCE FİLMLERİN BÜYÜTÜLMESİ VE NEM SENSÖRLERİNİN ÜRETİLMESİ - ORMAN, YUSUF (Fırat Üniveristesi, 2014)
Bu çalışmada, nano yapılı TiO2 numuneleri hidrotermal yöntem ile hazırlandı. Hazırlanan TiO2 numuneleri taramalı elektron mikroskobu(SEM), atomik kuvvet mikroskobu (AFM) ve FT-IR teknikleri ile karakterize edildi. Numunelerin optik band aralıkları 3.12-3.15 eV aralığında bulundu. Numunelerin elektriksel iletkenliği sıcaklığın fonksiyonu olarak ölçüldü. Kuartz kristal mikro terzi sensörleri hazırlandı ve sensörlerin duyarlılık özellikleri detaylı olarak analiz edildi. Elde edilen sonuçlar TiO2 nano parçacıklarının nem sensörü uygulamalarında kullanılabileceğini göstermiştir.

Growth of nanostructured TiO2 Thin Films and Fabrication of Humidity Sensors In this study nano structure TiO2 samples doped were prepared by hydrothermal method. The prepared TiO2 samples were characterized by scaning electron microscopy (SEM), atomic force microscopy(AFM) and Fourier transform infrared spectroscopy (FT-IR) techniques. The optical band gaps of the samples were found to be in the range of 3,12-3,15 eV. The electrical conductivity of the samples was measured as a function of temperature. The quartz crystal microbalance sensors were prepared and the sensing properties of the sensors were analyzed in detail. The optained results inthecate that TiO2 nanoparticles can be used in humidty sensor aplications.
Growth of nanostructured tio2 thin films and fabrication of humidity sensors
Keywords: Fizik ve Fizik Mühendisliği